Answers

2016-03-15T22:19:48+05:30
Given that
we should consider the A.P as the following
a-d , a, a+d
sum of the first terms = 42
a-d+a+d = 42
3a = 42
a = 14
then the product of the three terms = 2618
(a-d)(a)(a+d) = 2618
a³-ad² = 2618
(14)² - 14(d)² = 2618
2744 - 14d² = 2618
14d² = 126
d² = 9
d = 3
first term = 14
common difference = 3 
first term = 14
second term = a+d
                      =14+3 = 17
third term = a+2d
                 =14+2(3) = 14+6  = 20
0
make brainlist please
sorry just change in the last of this sum